Intrinsic, instrumental and relational values behind nature’s contributions to people preferences of nature visitors in Germany - Jana Kachler; María R. Felipe-Lucia; Roman Isaac; Aletta Bonn; Berta Martín-López (Ecosystems and People)
Protected areas not only provide biodiversity conservation but also offer a multitude of nature’s contributions to people (NCP), such as recreational opportunities. Visitors to these areas value nature and NCP for various reasons, potentially leading to different arguments for conservation planning. So far, research has neglected the heterogeneity of reasons why visitors value nature and NCP in natural areas. In this study, we identified NCP preferences and elicited diverse values underpinning those preferences, i.e. intrinsic, instrumental and relational values. We analysed 127 semi-structured interviews with nature visitors of three regions encompassing protected areas across Germany including Schorfheide-Chorin (North East), Hainich-Dün (Central), and Schwäbische Alb (South West). We found that relational values resonated more broadly than intrinsic and instrumental values. We also found a connection between NCP preferences and the values underpinning them: regulating NCP were mostly associated with care and stewardship, instrumental values and social responsibility. In contrast, non-material NCP were mostly associated with therapeutic values and aesthetic values. Moreover, we found that socio-demographic factors – i.e. age, gender, income, education – and sustainable consumption patterns influenced the expression of different values. For instance, intrinsic values resonated more broadly for women than for men. We showed geographic differences in NCP preferences and their corresponding values across the regions. The results show that NCP values and preferences can be diverse within stakeholder groups and that research approaches need to be chosen carefully to be able to reveal this diversity. We conclude that value pluralism is fundamental to understanding underlying mechanisms in NCP research.